Biplot and Procrustes Analysis of Poverty Indicators By Province in Indonesia in 2015 dan 2019 - Ade Eriyen Saputri; Admi Salma; Nonong Amalita; Dony Permana (Departemen Statistika Universitas Negeri Padang, 2024)
Poverty is one of the country's problems that the government should overcome. Poverty is influenced by several indicators. The success of a government can be seen from changes in poverty. This study compares the percentage of Indonesia's poverty indicators at the beginning of office (2015) and the end of office (2019) of one government period. The indicators that most affect the poverty rate in 2015 and 2019 are seen using biplot analysis while to measure the similarity and the magnitude of the percentage change in poverty from 2015 to 2019 can use procrustes analysis. The results of the biplot analysis show households that have access to decent and sustainable sanitation services as the indicator with the highest diversity in 2015 while in 2019 it is the percentage of youth (aged 15-24 years) not in education, employment or training and households that have access to decent and sustainable drinking water services. Kepulauan Riau, DKI Jakarta, DI Yogyakarta, and Bali are the provinces that have the highest values in almost all poverty indicators except the indicator of the percentage of youth (aged 15-24 years) not in education, employment or training. The results of the procrustean analysis show an increase of 9.7% in Indonesia's poverty indicators in 2019 compared to 2015. So it can be said that the two configurations are very similar.